A new genus and species of brachyuran crab (Crustacea, Decapoda) from the Aptian-Albian (Cretaceous) of the Araripe Sedimentary Basin, Brazil. (June 2022) - Santana, William; Tavares, Marcos; Muniz Martins, Carlos Antônio; Pereira Melo, José Patrício; Pinheiro, Allysson P.
Abstract: A new brachyuran crab genus and species, Chronocancer camilosantanai, is described from carbonatic concretions of the Romualdo Formation of the Santana Group, Araripe Sedimentary Basin, northeastern Brazil. Chronocancer camilosantanai n. gen. n. sp. is provisionally assigned to the Orithopsidae. The new genus is superficially suggestive of the orithopsid Bellcarcinus Luque, 2014 (Upper Aptian of Colombia), of which it differs by a combination of characters including: carapace longer than wide, longitudinally suboval, wider anteriorly; internal supraorbital tooth broad triangular; anterolateral margins toothless; carapace hepatic, gastric and cardiac regions devoid of tubercles. The new species is briefly compared to all other known brachyurans found in the Araripe Sedimentary Basin. Highlights: A new genus and species of brachyuran crab is described. This is the fourth crab species described from Romualdo Formation of the Araripe Basin. Comparisons are made with all known species and a discussion about the family position is made.